Adsorption and thermal evolution of [C1C1Im][Tf2N] on Pt(111) - Massicot, Stephen; Gezmis, Emine; Talwar, Timo; Meusel, Manuel; Jaekel, Simon; Adhikari, Rajan; Winter, Leonhard; Fernández Fernández, Cynthia; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2023)
In the context of ionic liquid (IL)-assisted catalysis, we have investigated the adsorption and thermal evolution of the IL 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C1C1Im][Tf2N]) on Pt(111) between 100 and 800 K by angle-resolved X-ray photoelectron spectroscopy and scanning tunneling microscopy. Defined amounts of IL in the coverage range of a complete first wetting layer were deposited at low temperature (100-200 K), and subsequently heated to 300 K, or directly at 300 K. At 100 K, the IL adsorbs as an intact disordered layer. Upon heating to 200 K, the IL stays intact, but forms an ordered and well-oriented structure. Upon heating to 250 K, the surface order increases, but at the same time STM and XPS indicate the onset of decomposition. Upon heating to 300 K, decomposition progresses, such that 50-60% of the IL is decomposed. The anion-related reaction products desorb instantaneously, and the cation-related products remain on the surface. Thereby, the surface is partly passivated, enabling the remaining IL to still be adsorbed intact at 300 K. For IL deposition directly at 300 K, a fraction of the IL instantaneously decomposes, with the anion-related products desorbing, opening free space for further deposition of IL. Hence, cation-related species accumulate at the expense of anions, until one fully closed wetting layer is formed. As a consequence, a higher dose is required to reach this coverage at 300 K, compared to 100-200 K.
CRIS-Team Scopus Importer:2023-11-17

Conformation Controls Mobility: 2H-Tetranaphthylporphyrins on Cu(111) - Kuliga, Jan; Massicot, Stephen; Adhikari, Rajan; Ruppel, Michael; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2020)
The adsorption behavior and the mobility of 2H-Tetranaphthylporphyrin (2HTNP) on Cu(111) was investigated by scanning tunneling microscopy (STM) at room temperature (RT). The molecules adsorb, like the structurally related 2HTPP, in the "inverted" structure with the naphthyl plane restricted to an orientation parallel to the Cu surface. The orientation of the four naphthyl groups yields altogether 16 possible conformations. Due to the existence of rotamer pairs, 10 different appearances are expected on the surface, and all of them are identified by STM at RT. Most interestingly, the orientation of the naphthyl groups significantly influences the diffusion behavior of the molecules on Cu(111). We identify three different groups of conformers, which are either immobile, medium or fast diffusing at RT. The mobility seems to decrease with increasing size of the footprint of the conformers on the surface.
CRIS-Team WoS Importer:2020-03-03

Coverage- and temperature-induced self-metalation of tetraphenyltransdibenzoporphyrin on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto Dos Santos, Alisson; Jaekel, Simon; Adhikari, Rajan; Gazetas, Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Lytken, Ole; et al. (Journal of Physics: Condensed Matter, 2025)
We have investigated the adsorption and self-metalation of free-base tetraphenyltransdibenzoporphyrin (2H-TPtdBP) on Cu(111) as a function of coverage and temperature using scanning tunneling microscopy, x-ray photoelectron spectroscopy, temperature programmed desorption, and density-functional theory calculations. At low coverages (<0.16 molecules nm-2), we observe isolated individual molecules with an inverted conformation and no self-metalation up to 363 K. At higher coverages, both the formation of ordered islands and self-metalation are observed over time already at room temperature, and accelerate upon heating to 363 K. At 423 K, complete self-metalation occurs for all coverages up to the completed first layer. By comparing our results for 2H-TPtdBP to the existing literature on other tetraphenyl-based porphyrins, we demonstrate how adsorption and self-metalation can be tailored by the choice of substituents.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DFT; porphyrins; self-assembly; self-metalation; STM; TPD; XPS

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan; De Campos Ferreirra, Rodrigo Cezar; Adhikari, Rajan; Massicot, Stephen; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Marbach, Hubertus; De Siervo, Abner; Steinrück, Hans-Peter (ChemPhysChem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20-terakis(4-cyanophenyl)porphyrin (2HTCNPP) with post-deposited Zn atoms and the targeted reaction product Zn-5,10,15,20-terakis(4-cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post-deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post-deposited Zn. We attribute this to metastable SAT ("sitting atop") complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.
CRIS-Team WoS Importer:2021-01-29

On the adsorption of different tetranaphthylporphyrins on Cu(111) and Ag(111) - Brox, Jan; Adhikari, Rajan; Shaker, Majid; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Jaekel, Simon; Steinrück, Hans-Peter (Surface Science, 2022)
We address the adsorption of 2H-tetranaphthylporphyrin (2HTNP) and 2H-tetranaphthylbenzoporphyrin (2HTNBP) on Cu(111) and Ag(111). The difference between the two molecules is that for 2HTNBP the pyrrole groups are replaced by isoindole groups. We were interested in the resulting differences in the adsorption behavior on the two surfaces, in particular the role of the naphthyl groups. The investigations are performed with scanning tunneling microscopy at room temperature (RT) and after heating treatments (500 and 600 K). On Ag(111), 2HTNP forms a commensurable superstructure at RT, which transforms to a denser packed, non-commensurable structure upon annealing. For 2HTNBP, individual molecules are observed on Cu(111) at RT, which exhibit different mobility. In contrast, on Ag(111) the formation of ordered 2HTNBP islands occurs, which are stabilized by T-type interactions. After heating to 500 K, these islands undergo a structural change to a denser packed structure, which is stabilized by π-π stacking of neighboring naphthyl groups.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Commensurability; Naphthyl functionalization; Porphyrins; Self-assembly; STM

Self-Assembled 2D-Coordination Kagome, Quadratic, and Close-Packed Hexagonal Lattices Formed from a Cyano-Functionalized Benzoporphyrin on Cu(111) - Adhikari, Rajan; Kuliga, Jan; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2021)
We investigated the adsorption of 2H-5,10,15,20-Tetracyanophenyl-Tetrabenzoporphyrin (2H-TCNPTBP) molecules on Cu(111) by scanning tunneling microscopy in ultrahigh vacuum at room temperature. Three types of network structures are observed to coexist on the surface. The first two, a porous Kagome lattice and a porous quadratic structure, are stabilized by cyano-Cu-cyano bonds with Cu adatoms; the third is a close-packed hexagonal network, with much weaker intermolecular H-bonds and dipole-dipole interactions of oppositely oriented cyano end groups. The coexistence of the three structures is attributed to very similar energetics. While the two metal-coordinated porous structures with identical molecular density are stabilized by the energy gain due to the network formation, the hexagonal network compensates the weaker intermolecular interactions by a factor of 2.3 higher molecular density; furthermore, kinetic stabilization might play a role. Our results show that cyano functionalization of benzoporphyrins gives rise to unusual two-dimensional self-Assembled lattice structures.
CRIS-Team Scopus Importer:2021-05-14

Structure and Conformation of Individual Molecules upon Adsorption of a Mixture of Benzoporphyrins on Ag(111), Cu(111), and Cu(110) Surfaces - Adhikari, Rajan; Brox, Jan; Massicot, Stephen; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (ChemPhysChem, 2023)
We investigated the adsorption behavior of a mixture of six 2H-tetrakis-(3, 5-di-tert-butylphenyl)(x)benzoporphyrins (2H-diTTBP(x)BPs, x=0, 1, 2-cis, 2-trans, 3, and 4) on Ag(111), Cu(111) and Cu(110) at room temperature by scanning tunneling microscopy (STM) under ultra-high vacuum conditions. On Ag(111), we observe an ordered two-dimensional square phase, which is stable up to 400 K. On Cu(111), the same square phase coexists with a stripe phase, which disappears at 400 K. In contrast, on Cu(110), 2H-diTTBP(x)BPs adsorb as immobile isolated molecules or dispersed short chains along the [1 (Formula presented.) 0] substrate direction, which remain intact up to 450 K. The stabilization of the 2D supramolecular structures on Ag(111) and Cu(111), and of the 1D short chains on Cu(110) is attributed to van der Waals interactions between the tert-butyl and phenyl groups of neighboring molecules. From high-resolution STM, we can assign all six 2H-diTTBP(x)BPs within the ordered structures. Moreover, we deduce a crown shape quadratic conformation on Ag(111) and Cu(111), an additional saddle-shape on Cu(111), and an inverted structure and a quadratic appearance on Cu(110). The different conformations are attributed to the different degree of interaction of the iminic nitrogen atoms of the isoindole and pyrrole groups with the substrate atoms.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 2H-diTTBP(x)BPs; benzoporphyrin; isoindole groups; scanning tunneling microscopy; self-assembly

Structure and Reactivity of the Ionic Liquid [C(1)C(1)Im][Tf2N] on Cu(111) - Adhikari, Rajan; Massicot, Stephen; Fromm, Lukas; Talwar, Timo; Gezmis, Emine; Meusel, Manuel; Bayer, Andreas; Jaekel, Simon; Maier, Florian; Görling, Andreas; Steinrück, Hans-Peter (Topics in Catalysis, 2023)
We studied the adsorption and reaction behavior of the ionic liquid (IL) 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C(1)C(1)Im][Tf2N]) on Cu(111) using non-contact atomic force microscopy (nc-AFM), scanning tunneling microscopy (STM), and angle-resolved X-ray photoelectron spectroscopy (ARXPS) in ultrahigh vacuum as a function of temperature, supported by density-functional theory (DFT) calculations. Our nc-AFM results for sub-monolayer IL films show that at 200 K, the IL self-assembles into highly ordered islands, with cations and anions arranged next to each other in a checkerboard-type phase. After extended annealing at 300 K, the structure transforms first to a hexagonal phase and then to a porous honeycomb phase. Simultaneously, many small, disordered islands are formed. Complementary ARXPS reveals no IL desorption until 300 K. However, a significant fraction of the IL is converted to a new species as deduced from new, strongly shifted peaks that develop in the XP spectra at around 275 K and grow with annealing time at 300 K. We correlate the remaining unshifted peaks to the ordered phases observed in nc-AFM and the shifted peaks to decomposition products, which appear as disordered islands in nc-AFM and STM. Upon further heating to 360 K, about 50% of the anions or their decomposition products desorb from the surface, while cation-related fragments mostly remain on the surface. From DFT, we obtain additional information on the structure of the ordered phases and the interaction of the IL with the substrate.
CRIS-Team WoS Importer:2023-05-05